All-Trans Retinoic Acid Inhibits Bone Marrow Mesenchymal Stem Cell Commitment to Adipocytes via Upregulating FRA1 Signaling. (31st January 2020) - Xie, Linjun; Zou, Liying; Chen, Jie; Liu, Youxue
Abstract : Obesity, caused by an increased number and volume of adipocytes, is a global epidemic that seriously threatens human health. Bone marrow mesenchymal stem cells (BMSCs) can differentiate into adipocytes. All-trans retinoic acid (atRA, the active form of vitamin A) inhibits the adipogenic differentiation of BMSCs through its receptor RARG. The expression level of FRA1 (FOS like 1, AP-1 transcription factor subunit) in atRA-treated BMSCs increased, suggesting that atRA-mediated inhibition of BMSCs adipogenesis involves FRA1. BMSCs were transfected with adenovirus overexpressing Fra1 (ad-fra1) or silenced for Fra1 (si-fra1) and then treated with atRA. BMSCs treated with atRA and treated with ad-fra1 showed decreased mRNA and protein levels of key adipogenic genes ( Pparg2, Cebpa ) and adipogenesis-associated genes ( Cd36, Fabp, Lpl, and Plin ); atRA had a stronger inhibitory effect on adipogenesis compared with that in the ad-fra1 group. Adipogenic gene expression in Fra1 -silenced BMSCs was significantly upregulated. Compared with that in the atRA group, the si-fra1 + atRA also upregulated adipogenic gene expression. However, compared with si-fra1, si-fra1 + atRA significantly inhibited adipogenic differentiation. Chromatin immunoprecipitation showed that RARG directly regulates Fra1 and FRA1 directly regulates Pparg2 and Cebpa . The results supported the conclusion that atRA inhibits BMSC adipogenesis partially through the RARG-FRA1-PPARG2 or the CEBPA axis or both. Thus, vitamin A might be used to treat obesity and its related diseases.